NEW PEDAGOGICAL APPROACHES TO TEACHING ECONOMICS (Scientific journal of the Fergana State University, 2025)
Economics is a scientific field that allows you to understand and manage the economic processes of society, it teaches students economic theories, methods and practices. Teaching this subject is aimed not only at the formation of economic knowledge, but also at developing in students the ability to analyze modern economic problems, make decisions and actively participate in socio-economic processes. Since the middle of the last century, various pedagogical approaches have been developing in teaching economics. This article discusses new pedagogical approaches to teaching economics, their importance and role in the modern education system.